Teaching program based on the communicative approach for Basic English Level learning as a foreign language in adult learners Chiclayo – 2016 - Usquiano Piscoya, María Magdalena (2017)
The research was oriented to design a Teaching Program Model based on the Communicative Approach for Basic English Level as a foreign language for adult learners, focused on undergraduate educators of Cesar Vallejo University -Chiclayo Campus, according to their learning preferences. To achieve this objective, a pre-test has been elaborated to evaluate the knowledge level of English language regarding the participants that constitute the sample and a questionnaire was adapted to gather their preferences on the learning strategies in relation to this language. The theoretical foundations addressed are the communicative approach, constructivism, learning styles, andragogy, and the learning-teaching process on a teaching approach. A population conformed by 179 undergraduate educators and the sample, constituted by 100 teachers was selected through a simple random sampling method. Thereupon, the data analysis was executed and the result discussion was done using Microsoft Excel and the 19th version of the SPSS software. With this information was processed the conclusions and the recommendations of this report. Immediately, this research carries out to design the Teaching Program Model based on the Communicative Approach for the English Basic Level as a foreign language for adult learners focused on undergraduate educators of Cesar Vallejo University -Chiclayo Campus, according to their learning preferences. Such program was validated based on experts judgment, and it is presented through this report as an educational contribution and a departure point for future research.